GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 13679 species occurrences available in GBIF matching the query: TaxonKey: Lepidium virginicum L. HasCoordinate: true HasGeospatialIssue: false. The dataset includes 13679 records from 259 constituent datasets: 1 records from Bioimages. 3 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 32 records from OEH Atlas of NSW Wildlife. 33 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 2 records from Phanerogamic Botanical Collections (S). 13 records from PRECIS (KwaZulu-Natal Herbarium). 5 records from University of Vienna, Institute for Botany - Herbarium WU. 1 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 14 records from IAC - Herbário do Instituto Agronômico de Campinas. 1 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 17 records from Naturalis Biodiversity Center (NL) - Botany. 18 records from PRECIS. 4 records from UTEP Plants (Arctos). 3 records from Computarización de las colectas del estado de Morelos depositadas en el Herbario HUMO de la Universidad Autónoma del Estado de Morelos. 2 records from SANT Herbarium vascular plants collection. 12 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 39 records from FLORIVON. 7 records from Herbario Universidad de Antioquia (HUA). 2 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 39 records from Some Plant Specimens from KUN, IBSC, NAS Herbarium in China from 1900 to 1950. 1 records from Shropshire Ecological Data Network database. 1 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 1344 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 33 records from The digitization of plant specimens of NTU. 28 records from Depuración de la colección y base de datos del Herbario CICY. Fase IV. 1 records from BioFokus. 1 records from Colección Herbario Universidad Católica de Oriente. 4 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 2 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 47 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 9 records from El banco de datos del Herbario HCIB en línea (Fase I): Implementación del Sistema Biótica. 3 records from Plantas de La Frontera (ecorregión 12.1.1.1), e inventario florístico del Rancho El Aribabi, municipio de Imuris, Sonora. 21 records from Plantae of Costa Rica (INBio). 2 records from Bases de datos del proyecto análisis de la riqueza y el endemismo de la flora de México, con fines de su conservación, usando grupos y métodos selectos. 1 records from Biodiversidad vegetal de la parte alta oeste de la cuenca del Chuviscar, Chihuahua. 46 records from Artportalen (Swedish Species Observation System). 1 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 1 records from MBM - Herbário do Museu Botânico Municipal. 10 records from Flora de las playas y dunas costeras de México. 5 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 7 records from Oskarshamn herbarium (OHN). 1 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 19 records from Données ONF Faune-Flore-Fonge. 1 records from Herbarium areqvipense (HUSA). 51 records from Australia's Virtual Herbarium. 81 records from CSIC-Real Jardín Botánico-Anthos. Sistema de Información de las Plantas de España. 2 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 2 records from Herbier de Strasbourg. 1 records from Vascular Plant Herbarium, UiB. 16 records from Kathryn Kalmbach Herbarium. 2296 records from Consortium of California Herbaria. 202 records from iNaturalist Research-grade Observations. 6 records from Base de datos de la distribución de la flora de la Reserva de la Biosfera Tehuacán-Cuicatlán. 127 records from CONN. 47 records from H.A. Stephens Herbarium. 18 records from Other BSBI Scottish data up to 2012. 14 records from Base de datos del Herbario CIQR de El Colegio de la Frontera Sur, unidad Chetumal. 1 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 18 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 1 records from Collection botanique Le Grand A. (BOUM). 1 records from ALCB - Herbário Alexandre Leal Costa. 2 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 460 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 8 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 25 records from naturgucker. 1 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 1 records from Freiburger GEO-Tag der Artenvielfalt. 1 records from Luderbusch. 1 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 30 records from Dutch Vegetation Database (LVD). 2419 records from INPN - Données flore des CBN agrégées par la FCBN. 1 records from ASE - Herbário da Universidade Federal de Sergipe. 58 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 58 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 3 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 23 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 24 records from Angiospermatatophytina Collection of Saitama Museum of Natural History. 3 records from Tiroler Landesmuseum Ferdinandeum. 8 records from IBF Monitoring of Vascular Plants. 48 records from Inventario florístico de los cerros San Martí y El Patol en el semidesierto queretano. 253 records from Tropicos Specimen Data. 12 records from BRERC species records recorded over 15 years ago. 1 records from Naturhistorisches Museum Mainz, Botanical Collection. 2 records from Botanical Research Intitute of Texas. 21 records from Natural History Museum (London) Collection Specimens. 5 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 617 records from Waarnemingen.be - Non-native plant occurrences in Flanders and the Brussels Capital Region, Belgium. 12 records from Inventario florístico de la Sierra de San Carlos, Tamaulipas. 1 records from Inventario florístico de la Frailescana (zona focal), Chiapas, México. 4 records from Flora del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 6 records from Flora vascular del cerro El Zamorano. 1 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México. 38 records from Base de datos del Herbario de la Unidad Académica de Agronomía de la Universidad Autónoma de Zacatecas. 8 records from Flora-On: occurrence data of the flora of mainland Portugal. 2 records from Inventario florístico y faunístico del Parque Nacional Barranca del Cupatitzio, Michoacán. 1 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_1. 4 records from Plantas exóticas del centro de México y obtención de imágenes para una flora virtual de malezas. 3 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 9 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 2 records from Formación del banco de datos del herbario (UCAM). 4 records from Flora del Parque Nacional Pico de Tancítaro, Michoacán. 5 records from Catálogos florísticos de México por entidad federativa e información etnobotánica de la Colección del Herbario Nacional Biól. Luciano Vela Gálvez (INIF). 6 records from Florística de áreas protegidas en el estado de Durango. 31 records from Base de datos sobre la flora de Durango. 2 records from Inventario florístico de la Sierra de Huautla, Morelos. 13 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 2 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 3 records from Estudio etnobotánico de las malezas útiles presentes en diferentes agroecosistemas en el municipio de Santa María Tecomavaca, Valle de Tehuacán-Cuicatlán, México. 4 records from Flora y vegetación de la Sierra de San Carlos en el municipio de San Nicolás. 8 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 46 records from NMNH Extant Specimen Records. 1 records from Universität Salzburg. 6 records from The Himalayan Uplands Plant database (HUP Version 1). 11 records from Mountain Invasion Research Network (MIREN) survey. 3 records from Canadian Museum of Nature Herbarium. 119 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 1 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 1 records from Herbarium (ICEL). 1 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 3 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 5 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 5 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 7 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 1 records from Jardín Botánico de Córdoba: Herbarium COA. 11 records from Aranzadi Zientzi Elkartea. 3 records from Universitat de Girona: HGI-Cormophyta. 1 records from CIBIO, Alicante:ABH-GBIF. 3 records from Herbário João de Carvalho e Vasconcellos, I.S.A./U.L.. 2 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 1 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 1 records from Institut Botanic de Barcelona, BC. 69 records from Brassicaceae of Canada. 12 records from herbario. 16 records from Plant Specimens of Kurashiki Museum of Natural History. 20 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 23 records from Vascular Plant Collection. 15 records from DAV UC Davis Center for Plant Diversity. 36 records from Herbarium (UNA). 58 records from Actualización de las bases de datos del Herbario XAL. Fase III. 1 records from Herbarium Berolinense. 588 records from Observations du Conservatoire botanique national du Bassin parisien.. 70 records from Biologiezentrum Linz. 1 records from United States National Plant Germplasm System Collection. 11 records from USU-UTC Specimen Database. 2 records from Herbarium de Geo. B. Hinton, México. 1 records from Vascular Plants Collection of Sagamihara City Museum. 2 records from Harvard University Herbaria. 2 records from inatura - Erlebnis Naturschau Dornbirn. 11 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 6 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 5 records from Kochi Prefectural Makino Botanical Garden. 24 records from Biodiversitätsdatenbank des Landes Salzburg. 5 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from LaBoOb02. 1 records from Gemeinde Sursee. 1 records from Freiburger Tag der Artenvielfalt. 1 records from 4. GEO-Tag in Eberbach. 1 records from Bergkamen- Bergehalde Großes Holz. 1 records from Lindau im Bodensee. 1 records from Eppingen und Umgebung. 26 records from USF Herbarium. 48 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 8 records from Atlas Flora Danica. 6 records from Scottish SNH-funded BSBI records. 51 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 53 records from Field Museum of Natural History (Botany) Seed Plant Collection. 1 records from MPM Milwaukee Public Museum Herbarium. 77 records from Belgian IFBL Flora Checklists (1939-1971). 62 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 1 records from EEIKO Base de datos sobre plantas invasoras. 1 records from Freiburger Netzwerk Artenvielfalt. 1 records from Colorado State University Herbarium. 77 records from R. L. McGregor Herbarium Vascular Plants Collection. 1 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 126 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 18 records from Gunma Museum of Natural History, Vascular Plant Specimen. 8 records from Biological and palaeontological collection and observation data MNHNL. 47 records from Botany Division, Yale Peabody Museum. 1 records from Tag der Artenvielfalt im Taubental. 1 records from Herbarium Senckenbergianum (FR). 1 records from MEXU/Flora de Oaxaca. 10 records from Database of Native Plants in Taiwan. 9 records from Flora (vascular) y fauna (aves) de los Parques Nacionales del estado de Baja California: Constitución de 1857 y Sierra San Pedro Mártir. 1 records from Inventario florístico y faunístico del Parque Nacional Barranca del Cupatitzio, Michoacán. 46 records from Herbarium of Taiwan Forestry Research Institute. 66 records from Etapa final de la captura y catalogación del Herbario del Instituto de Ecología, AC, Centro Regional del Bajío. 2 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 32 records from Banco de datos florísticos del Herbario CHAP. 2 records from WII Herbarium Dataset. 8 records from National vegetation diversity inventory and mapping plan. 7 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 11 records from Integración de bases de datos, actualización y sistematización de la colección de flora del Herbario Eizi Matuda (HEM). 128 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 29 records from Bosque Mesófilo de Montaña de México. 11 records from Flora d'Andorra. 84 records from Lund Botanical Museum (LD). 17 records from Plantas vasculares de la Sierra Tarahumara -listado florístico, etnobotánico e histórico-. 1 records from Natural Resources Wales Regional Data : Mid-Wales. 1 records from TEPB - Herbário Graziela Barroso. 27 records from USF Herbarium. 1 records from Norwegian Species Observation Service. 1 records from HST - Herbário Sérgio Tavares. 7 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 11 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 8 records from LERN Records. 2 records from Inventario florístico en la zona de Bahía Magdalena e islas adyacentes, Baja California Sur. 9 records from University of Florida Herbarium (FLAS). 12 records from Bernice P. Bishop Museum. 2 records from FURB - Herbário Dr. Roberto Miguel Klein. 155 records from Carnet en Ligne. 1 records from CRI - Herbário Pe. Dr. Raulino Reitz. 1 records from Flora vascular y endemismos de las partes altas de varios macizos montañosos de Querétaro y norte de Michoacán-1ra Fase. 34 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 1 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 3 records from Actualización de la base de datos sobre la flora de la Reserva de la Biósfera Sierra de Manantlán, Jalisco-Colima, México. 6 records from Michigan State University Herbarium Vascular Plants. 6 records from Estudio florístico de la Sierra de Pachuca, Hidalgo, México. 1 records from La flora útil de dos comunidades indígenas del Valle de Tehuacán-Cuicatlán: Coxcatlán y Zapotitlán de las Salinas, Puebla. 2 records from Flora of Worcestershire. 77 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 2 records from Conservación del germoplasma vegetal en las regiones áridas y semiáridas de México. Fase 5. 13 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 5 records from Base de datos computarizada del herbario CIB, Instituto de Investigaciones Biológicas, Universidad Veracruzana. 13 records from BODATSA: Botanical Collections. 4 records from Incremento de los bancos florístico y etnobotánico de la Península de Yucatán. 6 records from Vascular plant herbarium, NTNU University Museum. 19 records from Données ONF Faune-Flore-FOnge. 2 records from Vascular Plants, Field notes, Oslo (O). 74 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 13 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 2 records from UB - Herbário da Universidade de Brasília. 6 records from Green Plant Herbarium (TRT). 4 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 15 records from Actualización e incremento de la base de datos del Herbario de la Benemérita Universidad Autónoma de Puebla. 3 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 3 records from Miscellaneous Vascular Plants. 21 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 21 records from Allan Herbarium (CHR). 1 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 151 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 6 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 1 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 16 records from Vascular Plant Herbarium, Oslo (O). 2 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 1467 records from Flora von Deutschland (Phanerogamen). 7 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 20 records from E. C. Smith Herbarium (ACAD). 25 records from Sistematización del Herbario Nacional Forestal Biól Luciano Vela Gálvez. 2 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 2 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 2 records from Fusión y actualización de las bases de datos del Herbario de la Facultad de Ciencias, UNAM (FCME), Guerrero. 2 records from Geneva Herbarium – General Collection (G). 27 records from Welsh BSBI data (ex-VPDB dataset) at hectad resolution. 11 records from Nijmegen Natural History Museum (NL) - Herbarium. 6 records from Some Plant Specimens from PE Herbarium in China from 1900 to 1950. 33 records from CAS Botany (BOT). 10 records from Atlas des plantes vasculaires de Lorraine. 20 records from Computarización de la base de datos del Banco Nacional de Germoplasma Vegetal - Fase 2. 3 records from HRCB - Herbário Rioclarense. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences